Drying of mangoes (Mangifera indica L. cv. Palmer) at changeable temperature conditions—Effects on energy consumption and quality of the dehydrated fruit - Amado, Laís Ravazzi [UNESP]; Silva, Keila de Souza; Mauro, Maria Aparecida [UNESP] (Wiley, 2021)
This study evaluated the influence of heat input change on the drying kinetics, energy consumption, the color, and carotenoid retention during the drying of mangoes. The drying conditions in the first stage were 95°C for 40 min and 80°C for 40 min, so that the surface temperatures of the fruit at the end of this stage were around 60°C. The temperatures of the second stage and corresponding continuous drying (control) were 70 and 60°C. As a result, the thermal intermittence influenced the drying kinetics, causing significant reductions in the overall process time and providing energy savings when compared to continuous drying. The color parameters did not show relevant changes as result of the intermittent drying while good carotenoid retention was obtained in intermittent conditions, when the second stage was 60°C. Therefore, the carotenes were more sensitive to a temperature of 70°C, which highlights the importance of limiting the temperature of the mango to 60°C during the two drying stages to better preserve the quality of the dehydrated fruit. Moreover, the high air temperatures used in the first stage were advantageous for reducing the overall process time and providing energy saving. Practical Applications: Drying is an operation well known for the food industry. However, in so many cases, dryers are not designed with energy consumption in mind. Moreover, simple procedures can bring savings in convective drying, as shown in the present study, where the application of two-stages in the convective drying of mangoes was advantageous to reduce the overall drying time and provide energy savings in relation to continuous drying. Besides that, good carotenoid retention was obtained using low temperature (60°C) at the second stage. The results can be useful for design of dryers and drying process, considering different temperatures. Intermittent drying of high moisture foods by varying the drying air temperature can be applied both on an industrial scale, in continuous belt dryers or in tunnel dryers, and on a small scale, using two or more dryers with different temperatures.